Regulation of Polycomb group complexes by the sequence-specific DNA binding proteins Zeste and GAGA - Mulholland, Niveen M. (Cold Spring Harbor Laboratory Press, 2003)
Repression and activation of the expression of homeotic genes are maintained by proteins encoded by the Polycomb group (PcG) and trithorax group (trxG) genes. Complexes formed by these proteins are targeted by PcG or trxG response elements (PREs/TREs), which share binding sites for several of the same factors. GAGA factor and Zeste bind specifically to PREs/TREs and have been shown to act as both activators and repressors. We have used purified proteins and complexes reconstituted from recombinant subunits to characterize the effects of GAGA and Zeste proteins on PcG function using a defined in vitro system. Zeste directly associates withthe PRC1 core complex (PCC) and enhances the inhibitory activity of this complex on all templates, with a preference for templates withZeste binding sites. GAGA does not stably associate with PCC, but nucleosomal templates bound by GAGA are more efficiently bound and more efficiently inhibited by PCC. Thus Zeste and GAGA factor use distinct means to increase repression mediated by PRC1.